1.9 Reflection across the x-axis: y=f(x)y = -f(x)

Reflection across the x-axis: y=f(x)y = -f(x)

The concept behind the reflections about the x-axis is basically the same as the reflections about the y-axis. The only difference is that, rather than the y-axis, the points are reflected from above the x-axis to below the x-axis, and vice versa.

Lessons

    • a)
      Sketch the following functions:
      y=(x4)3y = {\left( {x - 4} \right)^3} VS. y=(x4)3 - y = {\left( {x - 4} \right)^3}
    • b)
      Compared to the graph of y=(x4)3y = {\left( {x - 4} \right)^3}:
      • the graph of y=(x4)3 - y = {\left( {x - 4} \right)^3} is a reflection in the ___________________.
    • a)
      y=f(x)y = - f\left( x \right)
    • b)
      In conclusion:
      (y)(y)\left( y \right) \to \left( { - y} \right): reflection in the ____________________ ? all yy coordinates ______________________________.
Teacher pug

Reflection across the x-axis: y=f(x)y = -f(x)

Don't just watch, practice makes perfect.

We have over 1960 practice questions in Pre-Calculus for you to master.